Diagnosis of Calagasma Bergroth and Epipedus Spinola with description of Calagasma eclipsa sp. nov. and Epipedus rolstoni sp. nov. (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) - Lupoli, Roland (Zootaxa, 2016)
The genus Calagasma Bergroth synonymized with the genus Epipedus Spinola by Rolston (1987) is reinstated. The diagnostic characters of the genus Calagasma are redefined, pictures of the Calagasma margarita syntype and recently collected specimens from French Guiana, including males hitherto unknown are presented. Calagasma eclipsa, a new species from French Guiana is described. Epipedus is redescribed and a new species Epipedus rolstoni is described.